Structure, Synthesis and Inhibition Mechanism of Nucleoside Analogues as HIV‐1 Reverse Transcriptase Inhibitors (NRTIs) - Yoshida, Yuki; Honma, Masakazu; Kimura, Yasuaki; Abe, Hiroshi (ChemMedChem, 2021)
Acquired immunodeficiency syndrome (AIDS) is caused by infection with the human immunodeficiency virus (HIV). Although treatments against HIV infection are available, AIDS remains a serious disease that causes many deaths annually. Although a variety of anti‐HIV drugs have been synthesized and marketed to treat HIV‐infected patients, nucleoside analogue reverse transcriptase inhibitors (NRTIs), which mimic nucleosides, are used extensively and remain a subject of interest to medicinal chemists. However, HIV has acquired drug resistance against NRTIs, and thus the struggle to find novel therapies continues. In this review, we trace the trajectory of NRTIs, focusing on the synthesis, mechanisms of action and applications of NRTIs that have been developed. Deceiving HIV‐1: This review focuses on the structure, synthesis and inhibition mechanism of HIV‐1 nucleoside analogue reverse transcriptase inhibitors (NRTIs). A number of drugs that have been marketed and will be approved for the treatment of AIDS are summarized, with a focus on synthesis and mechanisms of action; this will provide useful information for the development of novel NRTIs against HIV‐1.